Distribution and origin of ground ice in University Valley, McMurdo Dry Valleys, Antarctica. Issue 2 (1st December 2016) - Lapalme, Caitlin; Lacelle, Denis; Pollard, Wayne; Fisher, David; Davila, Alfonso; Mckay, Christopher P.
Abstract: Ground ice is one of the most important and dynamic geologic components of permafrost; however, few studies have investigated the distribution and origin of ground ice in the McMurdo Dry Valleys of Antarctica. In this study, ice-bearing permafrost cores were collected from 18 sites in University Valley, a small hanging glacial valley in the Quartermain Mountains. Ground ice was found to be ubiquitous in the upper 2 m of permafrost soils, with excess ice contents reaching 93%, but ground ice conditions were not homogeneous. Ground ice content was variable within polygons and along the valley floor, decreasing in the centres of polygons and increasing in the shoulders of polygons towards the mouth of the valley. Ground ice also had different origins: vapour deposition, freezing of partially evaporated snow meltwater and buried glacier ice. The variability in the distribution and origin of ground ice can be attributed to ground surface temperature and moisture conditions, which separate the valley into distinct zones. Ground ice of vapour-deposition origin was predominantly situated in perennially cryotic zones, whereas ground ice formed by the freezing of evaporated snow meltwater was predominantly found in seasonally non-cryotic zones.